Potential distribution of podocnemis lewyana (reptilia:podocnemididae) and its possible fluctuation under different global climate change scenarios (2014)
We implemented a species distribution modelling approach to establish the potential distribution of Podocnemis lewyana, to explore the climatic factors that may influence the species’ distribution and to evaluate possible changes in distribution under future climate scenarios. The distribution models predicted a continuous distribution from south to north along the Magdalena River, from Rivera and Palermo in the department of Huila to the departments of Atlántico and Magdalena in the north. Temperature was the variable most influential in the distribution of P. lewyana; this species tends to be present in warm regions with low temperature variability. The distribution model predicted an increase in the geographic range of P. lewyana under climate change scenarios. However, taking into account the habitat preferences of this species and its strong association with water, this result should be treated with caution since the model considered only terrestrial climatic variables. Given the life history characteristics of this species (temperature-dependent sex determination, high pivotal temperature and a very narrow transition range) and the negative effect of changes in hydrological regimes on embryo survival, expansion of the potential distribution of P. lewyana in the future does not mean that the species will not be affected by global climate change.DISTRIBUCIÓN POTENCIAL DE (Podocnemis lewyana, REPTILIA: Podocnemididae) Y SU POSIBLE FLUCTUACIÓN BAJO ESCENARIOS DE CAMBIO CLIMÁTICO GLOBALEn este estudio se implementó el modelaje de distribución de especies para establecer el rango de distribución potencial de Podocnemis lewyana, explorar los componentes del clima que pueden influenciar dicha distribución y evaluar posibles fluctuaciones de su distribución bajo escenarios de clima futuro. Los modelos obtenidos predicen una distribución continua de sur a norte por todo el río Magdalena, desde los municipios de Rivera y Palermo en el departamento de Huila, hasta los departamentos de Atlántico y Magdalena en el norte. La temperatura fue el elemento del clima que más influyó en la distribución de P. lewyana; esta especie tiende a estar presente en climas cálidos y con poca variabilidad en la temperatura. El modelo de distribución transferido a los escenarios de clima futuro predicen un aumento en el rango geográfico de P. lewyana. Sin embargo, teniendo en cuenta las preferencias de hábitat de esta especie y su fuerte asociación con los cuerpos de agua, este resultado debe tomarse con cautela, dado que el modelo sólo tuvo en cuenta variables climáticas terrestres. Dadas las características de historia de vida de esta especie (presencia de determinación sexual dependiente de la temperatura, alta temperatura pivotal y un rango de transición de temperatura muy estrecho), y el efecto negativo de los cambios en los regímenes hidrológicos en la mortalidad embrionaria, la expansión del área potencial de P. lewyana en el futuro no significa que esta especie no vaya a verse afectada por el cambio climático global.